Alcune osservazioni sull’istituto del divorzio in Corea del Sud (Stato, Chiese e pluralismo confessionale, 2012)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione a stampa negli Annali della Facoltà di Giurisprudenza di Taranto, per i tipi della Casa editrice Cacucci di Bari.SOMMARIO: 1. Introduzione - 2. La disciplina del divorzio nel Codice Civile coreano e i relativi aspetti patrimoniali - 3. Fidanzamento, matrimonio, nullità e interruzione per morte del matrimonio - 4. La tutela dei figli nel divorzio - 5. Riforma del diritto di famiglia n. 7427/2005ABSTRACT: Some remarks on divorce in South Korea The Korean family law regulates two different procedures for divorce: divorce by agreement (which is used in cases where both spouses are agree to terminate the marriage) and judicial divorce. Closely related to divorce are different problems, because of which this institution has been repeatedly the subject of reforms; the most significant reforms are: the first one in 1991, which aims to achieve a way of equality between man and woman, then in 2005, which had as its goal to remove the "head of the family" system and the last one in 2007 made to realize an effective protection of children as the greatest victims of their parents’ divorce. The most innovative reform has been the law n. 7427 of 2 March 2005 (with eight points, four of which came into force immediately and the other in 2008). It deals essentially in abolish the head of the family system, on the ground that it was unconstitutional, because the system contains articles that infringe individual dignity and equality between sexes in marriage and so they are contrary to art. 36 of the Korean Constitution.PAROLE CHIAVE: Codice Civile coreano – Matrimonio - Divorzio – Tutela dei figli – Diritto di famiglia – Leggi di riforma